1992
DOI: 10.1115/1.2927987
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tip-Leakage Losses in Axial Turbines

Abstract: Existing methods for predicting the tip-leakage losses in turbomachinery are based on a variety of assumptions, many of which have not been fully verified experimentally. Recently, several detailed experimental studies in turbine cascades have helped to clarify the physics of the flow and provide data on the evolution of the losses. The paper examines the assumptions underlying the prediction methods in the light of these data. An improved model for the losses is developed, using one of the existing models as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…These losses can be reduced if the discharge coefficient is decreased. A discussion of the tip discharge coefficient for axial turbine blades is given by Heyes et al [10] or Willinger and Haselbacher [18]. Their results are valid for blades with flat tips as well as squealers.…”
Section: Fig 3 Blade Tip Geometrymentioning
confidence: 93%
See 1 more Smart Citation
“…These losses can be reduced if the discharge coefficient is decreased. A discussion of the tip discharge coefficient for axial turbine blades is given by Heyes et al [10] or Willinger and Haselbacher [18]. Their results are valid for blades with flat tips as well as squealers.…”
Section: Fig 3 Blade Tip Geometrymentioning
confidence: 93%
“…The blockage effect is proportional to the injection mass flow rate. Based on these findings, the discharge coefficient model without any tip injection, presented by Willinger and Haselbacher [18] will be extended to take into account the blade tip injection.…”
Section: Fig 3 Blade Tip Geometrymentioning
confidence: 99%
“…The leakage vortex has high total pressure loss and strong rotary motion. Yaras and Sjolander [6] mentioned from their earlier investigations that secondary loss which is attributed to passage vortex fell off quickly with clearance and at 2% clearance it accounted for an insignificant fraction compared with loss in the tip leakage flow. The passage vortex grows in size as it moves axially.…”
Section: C~ • D R (1)mentioning
confidence: 97%
“…With a suitable discharge coefficient, good predictions were then obtained for the gap mass flow rate. The model was subsequently used in a loss prediction method (Yaras and Sjolander, 1992) since it was found that tip-leakage losses are strongly dependent on the mass flow rate through the gap. The model is extended here to account for the effects of relative wall motion.…”
Section: Flow In the Gap Main Stream And Near The Tipmentioning
confidence: 99%